The Serious Challenge of Occult Hepatitis B Virus Infection-Related Hepatocellular Carcinoma in China - Xia, Renxiang; Peng, Jing; He, Jian; Jiang, Ping; Yuan, Chunyan; Liu, Xiaoli; Yao, Yunqing (Frontiers in Microbiology, 2022)
Background It is unknown how many people in China have chronic occult hepatitis B virus (HBV) infection (OBI) [chronic HBV infection with negative serum hepatitis B surface antigen (HBsAg) (N-HBsAg)]. Their clinical and virological characteristics, especially the correlation between the OBI and hepatocellular carcinoma (HCC), are still elusive and need to be investigated, including prevention, early diagnosis, and treatment strategies. Methods 138 patients with HCC related to OBI were screened from 698 patients of HCC associated with HBV infection, their characteristics of epidemiology, clinical, biochemistry, virology, diagnostics, and therapeutics were analyzed retrospectively. Furthermore, the correlation between virological features and clinical features was investigated. Results It was found that 19.8% (138/698) of patients with HBV-related HCC were OBI, of which 79.7% (110/138) were men, and 20.3% (28/138) were women. Most of the patients with OBI-related HCC were older men, and the median age was 63.2 years. In total 78.3% (108/138) of the patients had apparent right upper abdomen discomfort and/or pain and then sought medical examination, while 21.7% (30/138) of the patients were identified by health examination. A total of 10.9% (15/138) of the patients were admitted with chronic infection of HBV, and 2.2% (3/138) of the patients were admitted with a family history of hepatitis B. The alpha-fetoprotein (AFP) serum-positive rate was 39.1% (54/138). Tumor lesions >5.0 cm, with intrahepatic and/or extrahepatic metastasis, were found in 72.5% (100/138) of the patients. The diameter of the tumor in the Group of hepatitis B core antibody-positive [HBcAb(+)] and hepatitis B surface antibody-positive [HBsAb(+)] was 7.03 ± 3.76 cm, which was much smaller than 8.79 ± 4.96 cm in the Group of HBcAb(+) and HBsAb(−) (P = 0.035). Conclusion It is estimated that at least 21 million OBI patients live in China. HBcAb(+) was not only the evidence of chronic HBV infection but also a dangerous mark for surface antigen-negative patients. A semi-annual or annual medical checkup is essential for all OBI patients to identify HCC as early as possible. The hypothesis underlying our analysis was that hepatitis B surface antibody would prevent the progress of HCC and facilitate the clearance of HBV in patients with OBI. Thereby, the hepatitis B vaccine could be used to prevent severe disease consequences.